Rolling recrystallisation textures of commercial grades of low carbon steels - Flavell, T. (College of Aeronautics, 1966)
The work in progress concerning the study of rolling-recrystallisation textures in commercial grades of low-carbon steels is outlined, the influence of aluminium nitride precipitation and recovery phoenomena being the main lines of research. Results to date indicate that the retention of the (100) component of the rolling texture is more favoured during recrystallisation as the prior recovery times and temperatures are increased. Textural variations through the sheet thickness are also being studied, results to date being presented.